Mathematische Modelle in der Biologie: 22. November - 28. November 1981 - Hadeler, Karl-Peter; Jäger, Willi (Tagungsbericht, 1981)
W. Alt, Heidelberg; W. J. Ewens, Clayton; E. Frehland, Konstanz; B. Aulbach, Würzburg; G. Fusco, Roma; Stavros Busenberg, Povo; H.-R. Gregorius, Göttingen-Weende; Lloyd Demetrius, Göttingen-Nikolausberg; U. Grossmann, Dortmund; O. Diekmann, Amsterdam; K. P. Hadeler, Tübingen; W. Ebel, Tübingen; U. an der Heiden, Bremen; F. Hoppensteadt, Salt Lake City; Peter Klein, Praha; M. Iannelli, Povo; H. Kolb, Konstanz; W. Jäger, Heidelberg; D. Lauffenburger, Philadelphia; F. Jähnig, Tübingen; A. Leung, Cincinnati; K. Janáček, Praha; M. Levandowsky, New York; G. Karigl, Wien; P. Lory, München; J. Keener, Salt Lake City; D. Ludwig, Vancouver; M. C. Mackey, Montreal; U. Staude, Mainz; M. Mimura, Hiroshima; H. R. Thieme, Heidelberg; P. de Mottoni, Roma; M. A. Viergever, Delft; F. Rothe, Tübingen; H.-O. Walther, München; R. Schaaf, Heidelberg; P. Waltman, Iowa City; R. Schaback, Göttingen; A. Wörz, Tübingen; K. Schumacher, Heidelberg; M. Ziehe, Göttingen-Weende